Maternal immigrant status and signs of neurodevelopmental problems in early childhood: The French representative ELFE birth cohort. Issue 12 (2nd August 2019) - Schmengler, Heiko; El‐Khoury Lesueur, Fabienne; Yermachenko, Anna; Taine, Marion; Cohen, David; Peyre, Hugo; Saint‐Georges, Catherine; Thierry, Xavier; Melchior, Maria
Abstract : A growing body of evidence suggests that children of immigrants may have increased risks of neurodevelopmental disorders. However, evidence based on parent report and on very young children is lacking. We therefore investigated the association between maternal immigrant status and early signs of neurodevelopmental problems in a population‐based sample of 2‐year‐old children using standardized parent‐report instruments. We used data from the French representative Étude Longitudinale Française depuis l'Enfance birth cohort, initiated in 2011. The study sample included 9, 900 children of nonimmigrant French, 1, 403 children of second, and 1, 171 children of first generation immigrant women followed‐up to age 2 years. Neurodevelopment was assessed using the Modified Checklist for Autism in Toddlers (M‐CHAT) and an adaptation of the MacArthur‐Bates Communicative Development Inventories (MB‐CDI). In fully adjusted linear regression models, maternal immigrant status was associated with M‐CHAT scores, with stronger associations in children of first ( β ‐coefficient: 0.19; 95% CI 0.08–0.29) than second generation immigrants (0.09; 0.01–0.17). This association was especially strong among children of first generation immigrant mothers native of North Africa (vs. nonimmigrant French: 0.33; 0.16–0.49) and French‐speaking Sub‐Saharan Africa (0.26; 0.07–0.45). MB‐CDI scores were lowest among children of first generation immigrant mothers, particularly from mostly non‐francophone regions. Children of first generation immigrant mothers were most likely to have simultaneously low MB‐CDI and high M‐CHAT scores. Our findings suggest that maternal immigrant status is associated with early signs of neurodevelopmental difficulties, with strong variations according to maternal region of origin. Further research is necessary to test whether these associations persist and to determine the underlying mechanisms. Autism Res 2019, 12: 1845–1859 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: We asked immigrant and nonimmigrant mothers in France about early signs of neurodevelopmental problems in their 2‐year‐old children. Overall, we found that children of immigrants may be at higher risk of showing these early warning signs, as compared to children of nonimmigrants. This is in line with previous studies, which were based on doctors' diagnoses at later ages. However, our results differed depending on the mothers' regions of origin. We found the highest risks in children of first generation immigrants from North and French‐speaking Sub‐Saharan Africa, who also seemed especially at risk of neurodevelopmental problems combined with low language development.